Implementation of Association Rule Market Basket Analysis to Increase Sales Through Product Bundling Strategy at the Fashion Online Store - Buana, Arga; Vikaliana, Resista (Universitas Mercu Buana, 2024)
Athaku Online Store is an fashion online store that sells baby clothes and children's t-shirts by offering free design of images and writing on the products. The increase in the number of online stores has caused competition between online stores to become tighter, so that online stores need to develop business strategies by paying attention to consumer behaviour (Customer Relationship Management) which can be used as a basis to increase sales through product bundling strategies. The goal to be achieved in this research is to get an overview of the associations between products which will be used as a basis for making product recommendations to increase sales at the Athaku Online Store using data mining, namely association rules using an a priori algorithm. By collecting transaction data by consumers starting from January 1 to 30 September 2022 with a total of 4,229 transactions, analysis of the transaction data was carried out using a minimum support value of 0.15 and a minimum confidence value of 0.5 so that the results were obtained, namely 3 product association rules, which then validated the recommendations. by distributing questionnaires to 30 consumers of the Athaku online store. The product association rules that have been validated can be used as a basis for determining product bundling strategies in the Athaku online store. From the research results, it is known that there is an opportunity to increase sales for three products, namely Jumpers, Bloomers, and Bibs.